Threat and Intruder Models of Multi-agent Robotic System Using Police Office Model with Quantum Encryption* - et. al., Zakoldaev D. A., (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The subject of this study is to ensure the confidentiality of information in mobile robotic systems. To ensure the confidentiality of information, it is proposed to use quantum encryption methods. Existing developments in this area allow to ensure the correct generation of quantum keys between two elements. The paper considers the functioning of the multi-agent robotic system based on the Police Office Model, the general scheme of functioning and basic processes of information interaction are given. The authors consider the issue of the protection of the multi-agent robotic system by using quantum keys from various threats, offering a classification of threats. Based on the model of the multi-agent robotic system, an intruder model is proposed that includes the level of access of the intruder to the system and the period of interaction of the intruder on the system, based on the life-cycle model. As a result of the research, a model of generalized functioning of a mobile robotic system with encryption based on quantum keys, a threat model and an intruder model was proposed.